Complete Heart Block Following Anaphylaxis: A Case Report and Literature Review - Nergiz Aydin; Yakup Alsancak; Ahmet Soylu (Haseki Tıp Bülteni)
Allergic reactions can range from mild symptoms to life-threatening anaphylaxis, and they may involve significant cardiovascular consequences. Anaphylaxis can cause disturbances in the conduction system, including complete heart block. This case report describes a patient who developed complete heart block following the administration of cefixime, a third-generation cephalosporin. The condition required the insertion of a pacemaker during the patient’s follow-up. This report underscores the importance of monitoring and managing cardiovascular effects in patients experiencing severe allergic reactions, particularly when using certain antibiotics like cefixime.